RANCANG BANGUN SISTEM PENGUNCI MEKANIS PADA AUTOMATIC SLIDING DOOR DI AREA KEDATANGAN BANDAR UDARA ZAINUDDIN ABDUL MADJID- LOMBOK - Kurniawanto , Hari; Puji Astuti, Annisa; Restu, Aldo (Program Studi Teknik Mekanikal Bandar Udara, 2024)
An automatic door is a type of door that operates without manual intervention and can open by sliding (sliding door), swinging open (swing door), or rolling up (rolling door). While automatic doors may not seem significant compared to other types of equipment, they play an important role, particularly as a barrier between secure areas and public spaces. Upon observation, it has been noted that some automatic doors do not have a mechanical locking system in place, or are only equipped with a motorized locking system, making it possible to force the door open with bare hands. This presents a security risk, as unauthorized access to restricted areas, such as those in airports, can lead to illegal activities such as smuggling, theft, and sabotage. Therefore, it is crucial to ensure that the locking system of automatic doors functions optimally to prevent such security breaches